Orthogonal programming of heterogeneous micro-mechano-environments and geometries in three-dimensional bio-stereolithography. Issue 1 (December 2018) - Yin, Hang; Ding, Yonghui; Zhai, Yao; Tan, Wei; Yin, Xiaobo
Abstract Engineering heterogeneous micro-mechano-microenvironments of extracellular matrix is of great interest in tissue engineering, but spatial control over mechanical heterogeneity in three dimensions is still challenging given the fact that geometry and stiffness are inherently intertwined in fabrication. Here, we develop a layer-by-layer three-dimensional (3D) printing paradigm which achieves orthogonal control of stiffness and geometry by capitalizing on the conventionally adverse effect of oxygen inhibition on free-radical polymerization. Controlled oxygen permeation and inhibition result in photo-cured hydrogel layers with thicknesses only weakly dependent to the ultraviolet exposure dosage. The dosage is instead leveraged to program the crosslink density and stiffness of the cured structures. The programmable stiffness spans nearly an order of magnitude (E 2–15 kPa) within the physiologically relevant range. We further demonstrate that extracellular matrices with programmed micro-mechano-environments can dictate 3D cellular organization, enabling in vitro tissue reconstruction. Tuning the mechanical properties of extracellular matrix is of great interest in tissue engineering but spatial control over stiffness in hydrogels has been demonstrated in two dimensions only. Here the authors developed a layer-by-layer printing technique which uses oxygen inhibition to control the heterogeneous stiffness in 3D printed structures.